Coordination specificity in strength and power training - Leirdal, S.; Roeleveld, K.; Ettema, G. (International Journal of Sports Medicine, 2008)
In this study, we tested the hypothesis that specificity of inter-joint coordination in power training improves training effects. We compared two different training regimes, one with and one without the possibility to exploit the coordination between knee and ankle, on performance and coordination in maximal vertical jumping and explosive squat movements. 22 subjects were divided into two groups for a 5-week training study. One group (Tsingle) trained squats (SQ) and plantar flexions (PL) in separate activities and the other group (Tmulti) trained squats ending with plantar flexion in one movement (SQPL), three times a week.